The Increasing Motivation For Social Studies Content Using The Piston Model In Class V Elementary School Students - Zarkasi Noor, Muhammad; Cinantya, Celia (Berpusi Publishing, 2023)
This research is motivated by the problem of low learning activities, student motivation, which influences low social studies learning outcomes. An effort to overcome the problems that arose was to apply Piston learning through Classroom Action Research (PTK) which was carried out in 4 meetings in class V at SDN 1 Sumber Alaska with research objects of 20 students. The aim of this research is to describe teacher activities, student activities and student learning motivation as observed through observations and test results. The findings from this research indicate that teacher performance at meeting I reached 64% and continued to increase in meetings until it reached 96%. Student activity at the first meeting reached 50% and continued at each meeting until it reached 90%. Student learning motivation in I reached 50% and continued to increase at each meeting until it reached 90%. Student learning outcomes in all aspects continue to increase at each meeting until they reach a score of 70 according to the KKM so that students meet the criteria for completion. In connection with the findings and results of the research, it can be concluded that the Piston model teaching approach activities are able to improve creative thinking skills and student learning outcomes in social studies learning.